Pentingnya Media Pembelajaran di Sekolah Minggu: Refleksi Injil Matius - Nelly Nelly; Maya Lusiana Patunduk (STIPAK Malang, 2020)
Sunday school is an important part of church service, so it must be taken seriously. One of the preparations for teaching Sunday School is to provide learning media. The purpose of this research is to develop learning media based on the Gospel of Matthew in the learning process at Sunday School of GPdI